Software development for fetal heart rate monitoring system - Rafiq Azeem N. bin Rahmat Ameen N (2023)
This thesis presents a development of a fetal rate monitoring software using Microsoft Visual Basic 6.0. The software will run under a Microsoft Windows environment where users can interact with it. The primary function of the software is to display the fetal heart rate traces where the data fetched from a binary file.